Effect of dye modification on the sorption of copper by coconut husk - Low, K. S.; Lee, C. K.; Wong, S. L. (Taylor and Francis Group, 1995)
The ability of coconut husk and its dye-coated forms to remove Cu from aqueous solutions has been investigated at different concentrations and pH values. The effects of some common chelators and other metal ions on Cu sorption were also studied. The equilibrium data obey the Langmuir isotherms for the natural and dye-coated husk-Cu systems. Dye modification led to an enhancement in Cu sorption.